2018
DOI: 10.18632/oncotarget.24306
|View full text |Cite
|
Sign up to set email alerts
|

High infiltration of CD68+ macrophages is associated with poor prognoses of head and neck squamous cell carcinoma patients and is influenced by human papillomavirus

Abstract: Incidence of human papillomavirus (HPV)-related head and neck squamous cell carcinomas (HNSCCs) has increased over the last few decades. The reaction of the host immune system to these tumors remains biologically complex. Here, we investigated CD68+ macrophage numbers, reporting the prognostic value in comparison to other risk factors. We also examined CD68+ macrophage infiltration during disease progression regarding the impact of HPV infection, and we studied the role of HPV16-E6/E7 oncoproteins in CD68+ mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 39 publications
5
59
1
Order By: Relevance
“…However, significantly more intense infiltration of both the total macrophage pool and M2-like macrophages was found in HR-HPV-positive tumours compared to HPVnegative ones. Similar observations were described in the work of Seminerio regarding the total macrophage pool [37] and by Ryu et al [38] in relation to M2-like macrophages. In the first study, the authors also showed the significance of CD68 + macrophage infiltrates in tumour tissue as an independent factor of poor prognosis in regard to relapse-free survival and OS.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…However, significantly more intense infiltration of both the total macrophage pool and M2-like macrophages was found in HR-HPV-positive tumours compared to HPVnegative ones. Similar observations were described in the work of Seminerio regarding the total macrophage pool [37] and by Ryu et al [38] in relation to M2-like macrophages. In the first study, the authors also showed the significance of CD68 + macrophage infiltrates in tumour tissue as an independent factor of poor prognosis in regard to relapse-free survival and OS.…”
Section: Discussion/conclusionsupporting
confidence: 88%
“…Our data fits with other studies that show that exposure of mice to CSE induces macrophage recruitment in lung tissues and lung tumors, and that these macrophages are polarized to a protumorigenic phenotype (55,56). In HNSCC, macrophages promote cell migration, invasion and lymph node metastasis in in vitro and in vivo models, and are associated with worse outcome in patients (53,57,58). Moreover, studies show the correlation between the density of CAFs and TAMs with poor outcome in HNSCC (59,60).…”
Section: Discussionsupporting
confidence: 91%
“…HNSCC has abundant immune infiltration (51). CD68, a macrophage marker, is abundantly expressed in HNSCC tumor tissue, as opposed to normal tissue, and correlates with aggressive behavior, lymph node metastasis, increased incidence of extracapsular spread, and overall worse survival (52)(53)(54). We determined the effects of fibroblast CSE exposure on macrophage recruitment.…”
Section: Discussionmentioning
confidence: 99%
“…The polarisation of M1 and M2 macrophages are important for disease regulation. Previous studies have documented that activated macrophages are prominent in lung infection with bacteria [11] and viruses [12,13] as well as in lungs from smokers and chronic obstructive pulmonary disease (COPD) [14]. The main purpose of this study was to investigate the status of lung macrophages, as to M1/M2 subtypes in severe P. falciparum malaria patients with and without PE.…”
mentioning
confidence: 99%